Studi Kesadaran Beragama Remaja di SMAN 1 Cikarang Timur dalam Perspektif Psikologi Islam - Salsabila, Mela; Jadidah, Siti Rahma Sanatul; Nur Alvia, Verona; Miki, Fhadiyah; Batubara, Noor Azida (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2026)
Religious awareness among adolescents at SMA Negeri 1 Cikarang Timur faces challenges in the digital era, influenced by social media, online gaming, and peer interactions that disrupt consistent religious practices despite school programs like Rohani Islam and dhuha prayer. This study aims to analyze adolescents' preferences and perceptions toward religious awareness and identify influencing factors. Employing a qualitative descriptive approach, data were collected from a population of approximately 1,000 students and key teachers via purposive sampling of nine informants: two teachers and seven students from class XI C and gaming groups. Instruments included semi-structured interviews, participatory observation, and documentation, analyzed using Miles, Huberman, and Saldana's interactive model with triangulation for validity. Findings reveal inconsistent religious awareness, marked by cognitive understanding but practical procrastination due to family support gaps, digital distractions, and weak intrinsic motivation. In conclusion, strengthening religious awareness requires school-family-community synergy through habituation and positive digital utilization.